Student perceptions of active learning management in a database systems course: A Thai university comparative study - Budsara, Kridsada; Ratanaolarn, Thanin; Petsangsri, Sirirat (Edelweiss Applied Science and Technology, 2025)
This study investigated undergraduate students' perceptions of learning management in a Database Systems course and compared these perceptions between students with and without prior active learning experience. A questionnaire was administered to undergraduate students from the Faculty of Science at KMITL, selected via simple random sampling. The instrument demonstrated strong validity (IOC = 0.60-1.00) and reliability (α = 0.81-0.87). Data were analyzed using descriptive statistics and an independent samples t-test. Overall perception of learning management was moderate. Course content received the highest mean score, followed by the instructor, while assessment and evaluation received the lowest. Students familiar with active learning perceived course content, learning processes, and the overall learning environment significantly more positively than those unfamiliar with active learning. Prior knowledge of active learning positively influences student perceptions, suggesting that readiness and mindset are essential for modern pedagogical approaches. Educators should explicitly introduce active learning principles at the course outset. Curriculum developers should reform assessment strategies to align with active learning principles and ensure practical, real-world examples are embedded in teaching methodology.